THE INFLUENCE OF FINANCIAL LITERACY AND PERSONALITY TRAITS ON PERSONAL FINANCIAL MANAGEMENT BEHAVIOR AMONG STUDENTS AT MUHAMMADIYAH 5 JUNIOR HIGH SCHOOL SAMARINDA: Pengaruh Literasi Keuangan dan Kepribadian terhadap Perilaku Pengelolaan Keuangan Pribadi pada Siswa SMP Muhammadiyah 5 Samarinda - Indah Permatasari; Amalina Yusdianti (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study investigates the impact of financial literacy and personality factors on personal financial management behaviours among eighth-grade students at SMP Muhammadiyah 5 Samarinda. The study employed a quantitative descriptive methodology with a saturated sample of 60 pupils. Data were gathered via a four-point Likert scale questionnaire and analysed using descriptive statistics and multiple linear regression in SPSS 25. The findings indicate that financial literacy significantly enhances personal financial management behaviour, whereas personality factors exert no notable partial effect. Financial literacy and personality factors concurrently exert a substantial influence on personal financial management behaviour, with the model accounting for 40% of the variance. The results demonstrate that financial literacy significantly influences students' financial management behaviour, but personality factors have a comparatively lesser impact in this research environment. Consequently, enhancing financial literacy teaching in junior high schools is essential to promote sound financial practices among adolescents.